Trace determination of tetracyclines in water samples by capillary zone electrophoresis combining off‐line and on‐line sample preconcentration. Issue 9 (29th March 2016) - Moreno‐González, David; Lupión‐Enríquez, Isabel; García‐Campaña, Ana M.
Abstract : In this work, a sensitive and reliable method using capillary zone electrophoresis with UV detection has been developed for trace determination of tetracycline antibiotics in river, spring, and ground waters. A solid‐phase extraction method using Oasis HLB was applied for off‐line preconcentration and cleanup of water samples, in combination with an on‐line preconcentration methodology named large volume sample stacking with polarity switching. Different parameters were optimized in order to obtain an adequate separation combined with the highest sensitivity, using 75 mM sodium carbonate (pH 10) and 1 mM EDTA as separation buffer, applying a voltage of 25 kV at 25°C. The samples were injected in water at 1 bar for 1 min, applying then −25 kV and starting the sample stacking. Sample matrix removal from the capillary was controlled by monitoring the electric current (when the 95% of the separation current is reached the stacking process is completed). The applied voltage was then switched from negative to a positive value of 25 kV in order to separate the compounds. Under optimum conditions, sensitivity enhancement factors ranged from 303 to 428 for the studied compounds. The combination of both off‐line and on‐line preconcentration procedures provided a total sensitivity enhancement factor about 20 000, obtaining detection limits from 67 to 167 ng/L. The precision (intra‐ and interday), expressed as %RSD was below 12%. Recoveries obtained from river, spring, and ground waters ranged from 87 to 96%. Thus, this procedure is suitable for monitoring these compounds in water samples.